Magnetic properties of amorphous Co0.74Si0.26/Si multilayers with different number of periods - Kakazei, G.N.; Sobolev, N.A.; Carmo, M.C.; Pogorelov, Yu.G.; Saliuk, O.Y.; Golub, V.O.; Alameda, J.M.; Martin, J.I.; Velez, M.; Quiros, C.; Santos, N.M.; Sousa, J.B. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
Two sets of [Co0.74Si0.26(5 nm)/Si(s)]n amorphous films were prepared by magnetron sputtering: one in theform of multilayers with the Si spacer thickness s fixed at 3 nm, and the number of periods n varying from 1 to 10; and another one with only two periods and s varying from 3 to 24 nm (trilayers). In both series, theCo0.74Si0.26 layer thickness t was fixed at 5 nm. All the samples except the one with s = 24 nm demonstrate antiferromagnetic coupling. Their magnetic properties at room temperature were probed by magnetooptical transverse Kerr effect (MOTKE) and ferromagnetic resonance (FMR). The relative increase of the saturation magnetization Ms (for trilayers with respect to the one with s = 24 nm; for multilayers with respect to the single layer one) obtained from the FMR measurements was compared with the exchange coupling strength HJAF obtained from the MOTKE studies. HJAF and Ms dependencies vs n and s were found to be very similar to each other. Possible mechanisms of this similarity are discussed.